Translation & interpretation 1 - Pham, Vu Phi Ho (Đại học Quốc gia Tp. Hồ Chí Minh, 2017)
Bibliographical references p. 93 - 95; At head of title: HoChiMinh City open university. Faculty of Foreign Languages